Exploring EFL Learners’ Attitudes towards Digital Note-Taking’s and its Impact on their Listening Comprehension The Case of Master One Students at the Department of English, Laghouat University - Djihad, Ghalem; Korichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2025)
This study attempts to investigate the EFL learners’ attitudes toward digital note-taking and its impact on their listening comprehension in the Department of English at the University of Ammar Thelidji. The theoretical framework of this research is based on a set of theories that serve as a road map to fully comprehend the entire study. To achieve this work, an online questionnaire was distributed to 25 Master One ELT students who were randomly selected. A mixed-methods approach was employed, combining both qualitative and quantitative methods. The conclusion drawn from the results of this study is that learners believe that digital note-taking has a positive influence on their listening comprehension skills. Additionally, findings also confirm that EFL learners need such tools to ensure pedagogical improvements for both learners and educators, consequently enhancing learners’ listening comprehension abilities and overall academic performance. Moreover, the results revealed that learners show positive attitudes as they are engaged and motivated to learn new technological trends, such as digital note-taking